Inductive resonant power transfer and topology consideration - Adam, Ismail; Kadir, Kushsairy Abdul; Khan, Sheroz; Nordin, Anis Nurashikin; Mansor, Hasmah (Institute of Electrical and Electronics Engineers Inc., 2018)
This paper aims to study the performance of all basic inductive resonant wireless power transfer (WPT) topologies for power transfer efficiency, using the effect of circuit topology in affecting the coefficient of coupling. In the study, all the four basic inductive resonant wireless power transfer topologies are analyzed and simulated. The simple T-equivalent circuit is used to represent the system and MATLAB® are used as the backbone in the analysis. The analysis shows that the parallel-to-series and parallel-to-parallel topology configurations give the best power transfer efficiency. The results show that parallel to series and parallel to parallel average power transfer efficiency referring to coefficient coupling (k) are 81% and 80% respectively, compared to the series-to-parallel and series-to-series which are almost 70% accordingly. The study provides evidence of further system analysis for parallel to series and parallel-to-parallel WPT topologies. The results of the analysis would prove useful in furthering insight into its application such wireless battery charging of electric vehicles